Developing a Sustainable Educational Curriculum: Integration of Green Technology and Environmental Awareness in Schools - Satrio Binusa Suryadi; Risa Juliadilla; Redi Sigit Febrianto (PT. Sinergi Bersahaja Sejahtera, 2025)
Background. The growing urgency of climate change and environmental degradation demands an educational transformation that integrates sustainability principles into school curricula. Education plays a vital role in shaping students’ environmental awareness and their capacity to apply green technology for sustainable living. Purpose. This study aims to develop a sustainable educational curriculum that integrates green technology and environmental awareness in schools. Specifically, it explores how curriculum design, pedagogical approaches, and school culture can synergistically promote ecological literacy and responsible behavior among students. Method. Using a mixed-method design, the study involved curriculum experts, teachers, and students from ten pilot schools implementing environmental education. Quantitative data were collected through surveys measuring students’ environmental attitudes and literacy, while qualitative data were obtained from interviews and classroom observations to assess the practical integration of green technology in learning. Results. The findings reveal that integrating green technology—such as renewable energy simulations, recycling projects, and digital eco-learning platforms—significantly enhances students’ environmental knowledge and problem-solving skills. Furthermore, teacher training and school-wide sustainability policies were found to be strong mediators in the successful implementation of the curriculum. Conclusion. The study concludes that sustainable curriculum design combining green technology and environmental awareness fosters a holistic learning environment that aligns with Sustainable Development Goals (SDGs). Future research should focus on longitudinal assessment and scalability across diverse educational contexts.